Impact investing in action: A framework for sustainability - Kumar, Sunil Chenichery Thazhath; Chotia, Varun; Soni, Swati; Khandelwal, Vinay (International Journal of Management and Sustainability, 2023)
The Sustainable Development Goals (SDGs) are a set of goals designed to be a “blueprint to achieve a better and more sustainable future for all.” Despite being meticulous about achieving the SDGs, India’s overall SDG score is 61.9 out of 100. While multiple models and frameworks have been developed, a new concept that has gained currency is impact investing. Content analysis of academic journal articles was employed to analyze the terminology, definition, and similarities and differences in the use of the term impact investing. Impact investing helps to benefit society and the environment without the need to sacrifice financial returns. It attempts to address the global challenges of access to energy, potable water, basic hygiene, nutrition, health, and education by exploring innovative commercial solutions. The degree of sustainability achieved through impact investing depends upon the efficiency of the multidisciplinary team formed to conduct the due diligence to achieve the social and financial goals by paying equal attention to risk, value addition, impact, and investor expectations. This study builds a case for India, suggesting the execution strategy of impact investing as an answer to India’s sustainability conundrum.